CULTURAL HERITAGE PRESERVATION: THE ART OF TRADITIONAL WEAVING IS APPLIED NOT ONLY IN CLOTHING - Nieta Hidayani (Jurnal Impresi Indonesia, 2024)
Traditional weaving has long been an integral part of Indonesia's cultural heritage. However, over the years, this art form has not only been used to make traditional clothing. However, it has also been applied in various other fields. This research aims to understand the history and cultural context of the art of weaving, examine the techniques and materials used, encourage sustainable use, bridge between generations, and identify threats and challenges facing the preservation of traditional weaving arts. The method used in this research is qualitative research, where the author observes local weavers at Penenun. The ages of these weavers range from teenagers to adults. This is then continued with a study of social theory and a literacy study of related phenomena regarding traditional weaving arts which are applied not only to clothing as part of efforts to preserve the nation's cultural heritage. This article analyzes how weaving can be applied in various fields, such as decorative arts, interior design and other products. This shows the flexibility and relevance of weaving in a modern context. The conclusion of this article reflects hope for the future of traditional weaving arts.